Bacillus and Trichoderma as growth promoters of Eucalyptus urograndis (Research, Society and Development, 2023)
Reforestation with cloned plants of the genus Eucalyptus has been increasing in relation to the planted area throughout Brazil. The use of Bacillus bacteria as plant growth promoters is a promising alternative with positive effects on the development of roots and shoots of eucalyptus seedlings. Another alternative is the use of fungi such as those of the genus Trichoderma, which promote growth through the production of phytohormones. The objective of this study was to evaluate the effects of using Bacillus subtilis Bs08 and B. subtilis Bs10 and the fungus Trichoderma harzianum UFT-25 on the initial growth of Eucalyptus urograndis. Seedling height, root length, shoot and root dry mass were evaluated. Inoculation of B. subtilis Bs08 and B. subtilis Bs10 to the substrate provided significant height developments in all E. urograndis plants within 30 days after planting. T. harzianum showed efficiency as growth promoters of clonal seedlings of E. urograndis in nursery conditions, being quite effective in root length, dry mass of the aerial part and dry mass of the root at 30 and 60 days after planting. The inoculation of B. subtilis Bs08, B. subtilis Bs10 and T. harzianum UFT-25 to the substrate provided a positive effect on the accumulation of biomass of E. urograndis seedlings, showing that these microorganisms are growth promoters for this forest species.